No accident, comrade chance and design in Cold War American narratives - Belletto, Steven (New York ; Oxford : Oxford University Press, 2012)
Drawing on novels by Nabokov, Wright, Powers, DeLillo, Didion and others, 'No Accident, Comrade' examines the shaping influence of the Cold War's obsession with chance on post-World War II fictional form.
Includes bibliographical references and index.
Description based on print version record.
Keywords: American fiction -- 20th century -- History and criticism; Cold War in literature; Chance in literature; Political fiction, American -- History and criticism